Population biology of the Hilsa Shad Tenualosa ilisha (Hamilton, 1822) during migration to Shatt Al-arab River and southern Al-Hammar marsh, Basra-Iraq - Al-Mukhtar, Mustafa A.; Mutlak, Falah M.; Mahdi, Amal A. (Iraqi Journal of Aquaculture, 2021)
Hilsa Shad Tenualosa ilisha (Hamilton, 1822) is one of the most important commercial fish species in Iraq and the region. Fish samples were collected during March 2013-April 2014 from Shatt Al-arab Estuary in Al-FAW city, Abu al-Khasib city, Sinbad Island and south Al-Hammar marsh. The first individuals were caught during February with length ranging 30.5-35.4cm in the estuary and the Shatt al-Arab. Monthly changes were found in mean fish length. The estuary region showed a marked increase in the average length of fish during June and November. The age composition was 0-V+ year. Length-Weight relationships were y=0.0086x3.067 for females, y=0.0119x2.947 for males, y=0.0141x2.833 for juveniles, y=0.0098x3.01 for male and female and y=0.0093x3.0304 for the overall population. The average relative condition factor (Kn) for female was 1.07 (± 0.12) ranging from 0.61-1.04. For males it reached 1.09 (± 0.125) ranging between 0.72-1.47. For young the mean was 1.21 (± 0.149) ranging from 0.66 to 1.73. The proportional size distribution showed that stock length was 13 cm, whereas the calculated specified lengths of Hilsa shad were 23, 29, 35 and 44 cm for quality, preferred memorable and trophy lengths respectively. The value of PSD Hilsa shad population was 60.7, which represents a balanced population consists a large proportion of breeding individuals. However, the decline in other specified lengths showed that Hilsa shad population was mostly medium-sized fishes, with RSD-T value of 3.8.